Neurolinguistic and acoustic analysis of articulatory impairments in Arabic speech disorders - Algaraady, Jeehaan; Mahyoob, Mohammad; Khan, Mohammad Zubair (Frontiers in Human Neuroscience, 2025)
BackgroundPharyngeal sounds, integral to Arabic phonetics, require precise vocal tract coordination, posing significant challenges for individuals with speech disorders.ObjectiveThis study investigates the neurolinguistic and acoustic characteristics of pharyngeal sound production in Arabic speakers with speech impairments, aiming to elucidate the impact of neurological disruptions on articulatory precision.MethodsA comparative study was conducted with 20 participants (10 with speech disorders, 10 with typical speech). Acoustic analysis, including spectrographic evaluation, was used to quantify deviations in pharyngeal sound production. Concurrently, neurolinguistic assessments, which included neurological evaluations, identified disruptions in neural pathways governing speech motor control.ResultsIndividuals with speech disorders exhibited significant neuromotor deficits, correlating with distinct acoustic deviations in pharyngeal sound production. These findings highlight the synergy of neurolinguistic and acoustic approaches in identifying underlying mechanisms of speech impairment.ConclusionBy integrating neurolinguistic and acoustic analyses, this study establishes a novel framework for diagnosing and treating pharyngeal sound disorders in Arabic speakers. The results inform targeted therapeutic interventions and the development of assistive technologies, advancing clinical outcomes in speech-language pathology.